2010
DOI: 10.1177/1477153509355632
|View full text |Cite
|
Sign up to set email alerts
|

Office workers’ daily exposure to light and its influence on sleep quality and mood

Abstract: "This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively." Hubalek, Sylvia; Brink, Mark; Schierz, Christoph: Office workers' daily exposure to light and its influence on sleep quality and mood URN:urn:nbn:de:gbv:ilm1-2014210273 To study the amount of light entering the eye and its effects on office workers, measurements were taken from 23 office workers over a period of seven con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 44 publications
9
75
0
Order By: Relevance
“…More direct evidence for this relation comes from aan het Rot et al (2008), who observed positive relations between bright light exposure and both arousal and pleasant mood, using an event-contingent recording protocol that allowed them to connect light exposures and the mood immediately following. Hubalek et al (2010), however, did not find any correlation between daily light…”
Section: Fundamentalsmentioning
confidence: 86%
See 2 more Smart Citations
“…More direct evidence for this relation comes from aan het Rot et al (2008), who observed positive relations between bright light exposure and both arousal and pleasant mood, using an event-contingent recording protocol that allowed them to connect light exposures and the mood immediately following. Hubalek et al (2010), however, did not find any correlation between daily light…”
Section: Fundamentalsmentioning
confidence: 86%
“…Hubalek, Brink, and Schierz (2010) found that office workers' light exposure patterns differed markedly between workdays and days at home; some of the days at home showed very low light exposures. The daily patterns for this sample were quite different from previously reported data for security guards in the same country (Koller, Kundi, Stidl, Zidek, & Haider, 1993).…”
Section: Application Tests For Circadian Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…al. recently reported a study on light levels to which office workers were exposed but was not able to conclude anything on the relationship between exposure to different light colours, and mood or cognitive performance [12]. Given the known strength of visual imagery as a cue to accessing memories [8], in this work we investigate whether colour alone can act as a sufficient prompt to help understand the lighting environments that a person is exposed to, thus being a valuable tool to the ergonomic research community.…”
Section: Related Workmentioning
confidence: 99%
“…orange and yellow are known as "warm" and blue, green and purple are known as "cold" and that warm colours are associated with happiness, pleasure, energy and stimulation while the cold colours are associated with calmness, healing, sadness. These chromatic effects from exposure to variations in colour temperature have theraputic properties and chromotherapy, the use of colour in therapy, has been practiced for millenia [12].…”
Section: Introductionmentioning
confidence: 99%